Deadlock-free buffer configuration for stream computing. (September 2017) - Li, Peng; Beard, Jonathan C; Buhler, Jeremy D
Stream computing is a popular paradigm for parallel and distributed computing, where compute nodes are connected by first-in first-out data channels. Each channel can be considered as a concatenation of several data buffers, including an output buffer for the sender and an input buffer for the receiver. The configuration of buffer sizes impacts the performance as well as the correctness of the application. In this article, we focus on application deadlocks that are caused by incorrect configuration of buffer sizes. We describe three types of deadlock in streaming applications, categorized by how they can be created. To avoid them, we first prove necessary and sufficient conditions for deadlock-free computations; then based on the theorems, we propose both compile-time and runtime solutions for deadlock avoidance.